Implementation of pancasila student profile strengthening project on the theme of entrepreneurship in elementary school students - Septiana Sari; Sigit Yulianto (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
P5 on the theme of entrepreneurship has been widely implemented. Still, there are challenges related to the lack of teacher readiness, lack of references, and lack of relevance to the local cultural context. This study aims to fill the gap by analyzing the implementation of P5-themed entrepreneurship based on traditional Semarang food and beverages. It focuses on identifying formed character values and supporting and inhibiting factors in its implementation. This research uses a descriptive qualitative method; the first data collection technique is a structured interview (principal, homeroom teacher, and students), the second is participatory observation of active participation type, and the third is documentation—data analysis model Miles and Huberman analysis. The findings in this study on the implementation of P5 start from the first stage of planning (the existence of a facilitator team, the level of readiness of the education unit, the design of the dimensions (theme and time allocation), teaching modules, strategy for reporting project results), the second stage of implementation (introduction stage, contextual stage, action stage, and reflection stage), the third stage of evaluation using process evaluation. The implementation of the P5 project shows four dimensions of character values that are formed in students, namely the Dimension of Faith, Fear of God, the Dimension of Mutual Cooperation, the Dimension of Critical Reasoning, and the Dimension of Independence. This shows that the P5 project is a practical learning approach. This success is influenced by supporting factors (teacher competence, parental involvement, and availability of natural resources) and inhibitors (limited time, funds), so efforts must be made to overcome them, such as time management and sponsorship of funds. This research is expected to increase the understanding of the P5 theme of entrepreneurship in the context of local culture so that it is sustainable and provide recommendations to improve the effectiveness of P5 implementation in schools.